Defect Engineering in Two Common Types of Dielectric Materials for Electromagnetic Absorption Applications. (8th May 2019) - Quan, Bin; Shi, Wenhao; Ong, Samuel Jun Hoong; Lu, Xiaochi; Wang, Paul Luyuan; Ji, Guangbin; Guo, Yufeng; Zheng, Lirong; Xu, Zhichuan J.
Abstract: Dielectric materials are greatly desired for electromagnetic absorption applications. Lots of research shows that conduction loss and polarization are two of the most important factors determining complex permittivity. However, the detailed dissipation mechanisms for the improved microwave absorption performance are often based on semiempirical rules, lacking practical data relationships between conduction loss/polarization and dielectric behaviors. Here, a strategy of introducing point defects is used to understand such underlying relationships, where polarizability and conductivity are adjustable by manipulating oxygen deficiency or heteroatoms. Based on first principles calculations and the applied oxygen‐deficient strategy, dielectric polarization is shown to be dominant in determining the permittivity behaviors in semiconductors. Meanwhile, the presented nitrogen doping strategy shows that conduction loss is dominant in determining the permittivity behavior in graphitized carbon materials. The validity of the methods for using point defects to explore the underlying relations between conduction loss/polarization and dielectric behaviors in semiconductor and graphitized carbon are demonstrated for the first time, which are of great importance in optimizing the microwave absorption performance by defect engineering and electronic structure tailoring. Abstract : A point defect strategy is introduced to investigate the underlying relations between the polarization/conduction loss and the complex permittivity. Dielectric polarization and conduction loss are found to play dominant roles in determining the complex permittivity of oxide semiconductors and graphitized carbon, respectively.